Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Dosen Negeri Pada Kopertis Wilayah V Yogyakarta - Pramudyo, Anung (208-7721)
This study examines the analysis factors that influence lectureâs performance at Kopertis V Yogyakarta.Â  Based on theory, several variables has been constructed. They are motivation, competency, leadership, and work environment justice are predictors of performance. This research was executed in Kopertis V Yogyakarta with 150 participants. The results supported motivation, competency, and leadership justice has strong predictive to lectureâs performance, but work environment has not influence to lectureâs performance at Kopertis V Yogyakarta.Â